Feeding India's babies: Trends and patterns in infant and young child feeding practices across India's states and districts - Nguyen, Phuong Hong; Avula, Rasmi; Pant, Anjali; Sarswat, Esha; Mathews, Pratima; Menon, Purnima (International Food Policy Research Institute, 2019)
Appropriate nutrition during early life, coming mainly from adequate infant and young child feeding (IYCF) practices, is essential for optimal growth and development. This Data Note describes the trends and patterns in key IYCF practices and food consumption patterns among children, summarizing state and district data from the third and fourth rounds of National Family Health Surveys (2006 & 2016).